PARTISIPASI MASYARAKAT DALAM PROGRAM KEBUN BIBIT RAKYAT (KBR) DI NEGERI KAITETU KECAMATAN LEIHITU KABUPATEN MALUKU TENGAH - Rahawarin, Nur Ilham; Silaya, Thomas M.; Sahupala, Andjela (MARSEGU : Jurnal Sains dan Teknologi, 2026)
The Kebun Bibit Rakyat (KBR) is a form of government effort to support forest and land rehabilitation activities through a community empowerment approach. This study aims to determine the level and forms of community participation in the KBR program in Kaitetu Village, Leihitu District, Central Maluku Regency. The method used in this study is a mixed method. Quantitative data will answer questions about the level of participation using a Likert scale, while qualitative data will answer questions about the forms of participation using a descriptive approach. The data collection methods were surveys and interviews. The results of the study show that the level of community participation in the KBR program is in the high category (80%). The criteria for participation are in the aspects of implementation (21%), planning (20%), utilization (20%), evaluation (19%), and motivation (20%). Respondent factors such as age, education level, occupation, income, and number of dependents influence the level of community participation in this program. Community participation can be grouped into five types, namely: participation in ideas, participation in labor, participation in property, participation in skills and expertise, and social participation. The success of the KBR is highly dependent on the active involvement of the community in all aspects of the program.